2020
DOI: 10.3390/rs12233849
|View full text |Cite
|
Sign up to set email alerts
|

Robust Data Fusion of UAV Navigation Measurements with Application to the Landing System

Abstract: To perform precise approach and landing concerning an aircraft in automatic mode, local airfield-based landing systems are used. For joint processing of measurements of the onboard inertial navigation systems (INS), altimeters and local landing systems, the Kalman filter is usually used. The application of the quadratic criterion in the Kalman filter entails the well-known problem of high sensitivity of the estimate to anomalous measurement errors. During the automatic approach phase, abnormal navigation error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…As of 2022, they are undergoing a revolutionary change. Russian researchers Kolosov K., Miller A., Miller B., believe that "The integration of data from various sensors is fundamental in the navigation of unmanned aerial vehicles [7]. The use of various sensors provides a comprehensive integrated observation of all-round objects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As of 2022, they are undergoing a revolutionary change. Russian researchers Kolosov K., Miller A., Miller B., believe that "The integration of data from various sensors is fundamental in the navigation of unmanned aerial vehicles [7]. The use of various sensors provides a comprehensive integrated observation of all-round objects.…”
Section: Resultsmentioning
confidence: 99%
“…This paper reviews and studies the works of foreign authors who study the possibility of introducing unmanned aerial vehicles in various fields of activity. A significant number of works are devoted to studies in the field of UAV infrastructure development, environmental and economic impact [1][2][3][4][5][6][7][8][9][10]. In the works of Ravil I. Mukhamediev, Adilkhan Symagulov, Yan Kuchin detail the variations of UAV application, listing and describing many options for their use, as well as describing the momentum from the introduction of drones in different areas [2].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the more widely used robot navigation methods include orbital navigation [1][2][3], inertial navigation [4][5], radar and visual navigation [6][7][8], etc. Most intelligent management robots of archives and books use orbits, markers and radar for navigation, such as laying tracks on the bottom of archival shelves, and the robot moves to the target archival shelf with the help of the tracks [9]; He Junjie et al studied a combination of vision and inertial navigation based on two-dimensional raster maps and inertial guidance combination of vision and inertial navigation to move by recognising QR codes in the storage room [10]; Hao Chen et al developed an intelligent book management robot that moves according to ground signs and marker lines, using sensors such as laser ranging and ultrasonic waves to achieve obstacle avoidance and line patrol [11][12]; Yan Chehai et al designed a book management robot whose path is identified by The recognition of the path of the library management robot designed by Yan Chehai et al is electromagnetically guided by pre-laying tracks on the ground and marked by installing RFID electronic tags at the locations of path nodes along the path [13]; in addition, the navigation of the robot can also be achieved by using cameras to detect landmarks [14].…”
Section: Introductionmentioning
confidence: 99%